Developing a Model for User Satisfaction Assessment in Energy Efficient Dwellings - Usma, Gokhan; Akinci, Nazli Ferah (UNIV POLITECNICA CATALUNYA, 2022)
Energy efficient dwellings are the buildings, energy consumption of which is minimized throughout their design, construction process and the whole life cycle. They are also defined as buildings which ensure healthy and productive environments for their users. However, the research on energy efficient dwellings in the literature, on the other hand, mainly addresses the topic in the context of environmental and economic sustainability. Residential user satisfaction, which is among the most important factors in the architectural design process, not sufficiently emphasized in the research on energy efficient dwellings. This study aims to determine the user satisfaction in energy efficient dwelling design and application studies comprehensively. Ultimately, it is aimed to develop a model of user satisfaction measurement which can be used throughout the design / construction process and afterwards to this end. Model components were derived from the analysis of various indicators. In this process, characteristics of energy efficient buildings, certification system criteria, housing quality standards and indicators obtained from the academic studies in the literature were taken into consideration. The assessment proposals formed in this way were applied to the pre-determined residential users, and then the indicators were reviewed. In the light of the data obtained through the field survey, the main themes and sub-indicators of the model were finalized. At the end of all the analyses, the explanatory power of the themes of the model were found satisfactory on the phenomenon that is aimed to measure.
Keywords: Energy efficient buildings; user satisfaction; energy efficient housing; satisfaction model; NEIGHBORHOOD SATISFACTION; Architecture; Urban Studies